The Essential Role of Tahfidz Boarding School in Internalizing Islamic Values: Study at Universitas Muhammadiyah Semarang - Iqbal Hidayatsyah Noor; Ali Imron; Rohmat Suprapto (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2024)
Islamic teaching values are an integral component of an Islamic educational institution. The value of Islamic teaching is also an indicator of success in the educational process at the institution. This also applies to Tahfidz Boarding school which has students with various backgrounds of study programs at Universitas Muhammadiyah Semarang (Unimus). Tahfidz Boarding school tries to instill Islamic values in every daily activity. Therefore, this study explains what Islamic education values are instilled and explains what methods are used at Tahfidz Boarding school. This type of research is field research. This research has primary data sources from all students who live in the Tahfidz Boarding school as well as being active students in each study program at Unimus. Other sources of this research are documents of student activities owned by Tahfidz Boarding school. The method of this research is deductive method with qualitative description data analysis with data collection method using observation, in-depth interview, and documentation. the conclusion of this research is the cultivation of Islamic teaching values in the men’s Tahfidz Boarding school of Unimus covers 4 values of ulumul qur'an, faith values, moral values, worship values and the methods used are five methods, namely lectures, practical methods, exemplary methods, and habituation methods.